Un confronto mancato: Walter Benjamin e Antonio Gramsci - La Rocca, Giulia (International Gramsci Journal, 2024)
This is the abstract of the Italian-language review of the volume Un confronto mancato: Walter Benjamin e Antonio Gramsci. The book (Macerata, Quodilbet, 2023) publishes the proceedings of a conference in Rome on the two Marxists held in Autumn 2022 which continues explicitly the earlier Vienna conference, the contributions to which are collected together in “International Gramsci Journal” 3(4), 2020. The proceedings fall into four sections. The first one deals with the philosophy of history and historical materialism, as elaborated by Gramsci in his “philosophy of praxis”; despite different starting points and apparently different assessments of historicism, there turns out in the end to be a convergence based on an anti-determinism. The second part focuses on revolution, counter-revolution and passive revolution, taking in the questions of the political subject and contemporary situations. Subjectivity is then the theme of the third section, as forms of life appropriate to the capitalist mode of production and as regards subjects attempting to emancipate themselves from this mode. The fourth section includes the two thinker-revolutionaries’ approaches to the question of the various types of intellectual, including their conceptions of the artistic vanguards, folklore and kitsch, and the translation of experience from one country to another.